Design of a Web-Based Pawn Management System Using the Waterfall Model at Enoni Cell - Syahrain, Chairil; A., Ghilman Yazid; Telaumbanua, Satinudi; Haryono, Wasis (PT.KARYA GEMAH RIPAH, 2025)
The rapid development of information technology encourages various sectors to adopt web-based systems to improve the efficiency and accuracy of data management. Enoni Cell is one of the companies engaged in the pawn sector, and therefore requires an integrated and easily accessible data management system. This study aims to design a web-based data management system inin a web-based data management system using the modelWaterfall software development. The Waterfall model is chosen for the systematic and structured stages, including needs analysis, system design, implementation, testing, and maintenance. This system is intended to not only improve data security and accuracy, but also to facilitate the process of recording, tracking and notification of data in deposit items. The results of this study are expected to provide an effective solution for Enoni Cell in sediment management, becoming more efficient and a reference for the development of similar systems in the future.